Statistical variation in Soil Nutrient Characteristics near Industrial Area of Mayiladuthurai Taluk of Mayiladuthurai District in Tamilnadu, India - et. al., P. Juliat Mary, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Surface soil samples were collected from the 0-50 centimeter depth and assessed the soil statistical variation in physico-chemical parameters. The soil grain class of the surface layer is (0-58 centimeter) of the shape. Soil samples of the experimental field were clay loam while it was clay for the subsurface (25-100 Centimeter) layers of the profile. The soil samples were air-dried, crushed and passed through a 2 mm sieve before analyzing it for Nitrogen, Phosphorus, Potassium, Organic Carbon, Organic Matter, pH and exchangeable bases. Soil pH was measured electrometrically with a glass electrode pH meter, EC was determined are by using Conductivity meter. Alkaline permanganate method, colorimetric method and Flame Photometer method is used to determine Macronutrients like N P and K. Walkley and Black method is used to determine Organic Carbon (OC) and Organic Matter (OM). While the SAR, ESP% and Cation Exchange Capacity (CEC) were calculated. Micronutrients like Zinc(Zn), Copper(Cu), Iron(Fe) and Manganese(Mn) were determined by using Atomic Absorption Spectrophotometer (AAS). Available Soil pH ranged between 7.3 to 7.9. The available Electrical Conductivity (EC) values ranged from 0.18 to 0.5dsm-1 within the range for optimal growth of plants. The ranges of available Organic Carbon are ranged between 0.23% and 0.36%, Organic matter content ranged between 0.46 and 1.11 %. Nitrogen 39.2 kg/ha-1 and 72.8 kg/ha-1 are lower than that of the control soil. Available Phosphorus is ranged between 30.00 kg/ha-1 and 67.5 kg/ha-1 and is slightly higher than that of the control soil and potassium 169 kg/ha-1 and 370 kg/ha-1 content were high respectively. Cu is available between 0.72 – 0.92 ppm and Cu was found in 100% sufficient in study area. Zn is noticed between 0.62-0.82 ppm and Zn was found in 100% deficient in study area. Mn is available between 1.18-3.92 ppm and Mn was found in 70.0% deficient and 30.0% sufficient in study area. The available concentration of Fe ranged between 3.09-4.88 ppm and Fe was found in 100% sufficient in the study area. Where all below the recommended limits. Our aim is to support the farmers to characterize the soil based on their nutrition status for best suited crops which can be used effectively for crop production and enhanced productivity [1]. The statistical variation in soil nutrition is focused in Mayiladuthurai taluk in the present study at industrial based agriculture land area of Mayiladuthurai taluk in Mayiladuthurai district. The recommendations of fertilizer can be made for the crops to enhance the productivity. Soil test assessed and recommends the application of balanced fertilizers would go a long way in enhancing soil fertility and productivity.